216 Cerebrospinal Fluid (CSF) Can Inhibit Wound Healing and Induce CSF Leaks by Inhibiting Angiogenesis. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Goldschmidt, Ezequiel; Gau, David; Schneck, Meghan; Roy, Partha; Gardner, Paul A
Abstract: INTRODUCTION: Mechanical pressure on dural or fascial wound edges exerted by cerebrospinal fluid (CSF) is thought to impair proper apposition of the wound borders and therefore prevent healing. Interestingly, it has been observed that the surgical tissues exposed to CSF do not bleed, exhibit smooth edges, and have no evidence of granulation tissue formation. This raises the question of whether the constituents of CSF themselves impair normal wound healing. However, the biochemical interaction of CSF with the healing process has not been investigated. Here, we hypothesize that CSF exhibits anti-angiogenic properties and therefore inhibits the healing process. METHODS: We used an in vitro model, in which human umbilical vein endothelial cells grow in a 3-dimensional scaffold. Normally these cells form capillary-like structures named cords. We exposed the model to varying concentrations of CSF vs Dulbecco's phosphate-buffered saline (DPBS), used as control. We then quantified cord length. To rule out potential direct cellular toxicity or a general effect on cell migration, we performed a "scratch test" on human fibroblasts exposed to the same CSF or DPBS concentrations. RESULTS: In all samples (n = 5) of CSF at 50, 75, and 100% volume/volume significantly diminished cell migration and subsequent formation of capillary-like structures compared to DPBS (used to control for dilutional effect) with a dose-dependent tendency. Cell migration remained unchanged in the fibroblast culture, suggesting that CSF specifically inhibits capillary formation. CONCLUSION: CSF inhibited cord formation with a dose-dependent tendency, implying that it contains signaling molecules that preclude angiogenesis. This effect was cell specific and not observed with fibroblasts. These experiments suggest that CSF, rather than acting as an inert bystander, may actively impair healing by inhibiting capillary formation. This could impact the understanding of postoperative leaks and the potential physiological role of cerebrospinal fluid in precluding neovascular formation in the subarachnoid space.